A CLINICAL AUDIT ON STATIN THERAPY AMONG TYPE 2 DIABETES MELLITUS PATIENTS ATTENDING PUSAT PERUBATAN ANGKATAN TENTERA (PPAT), SUNGAI BESI, MALAYSIA - Hassan, Hasliza Abu; Gupta, Ina Dutta; Ganesan, Shakti Vinayagan A/L; Hanafi, Syamsul Anwar Bin; Shaharuddin, Muhammad Aiman Bin; Azlan, Nur Fatin Fatni Binti Mohd; Baharudin, Nurul Ainnun Alesya Binti; Ramlee, Muhammad Amri Izzuddin Bin; Singh, Ishreena Kaur A/P Gurcharan; Awang, Siti Salmiah (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Type 2 Diabetes Mellitus (T2DM) patients are at higher risk of developing atherosclerotic cardiovascular disease (ASCVD), which leads to increased morbidity, mortality and use of healthcare resources. Therefore, the primary prevention of ASCVD can be achieved by prescribing the appropriate doses of statin therapy depending on the patient’s risk. This is a clinical audit on the use of statin therapy among type 2 Diabetes Mellitus patients at PPAT, Sungai Besi. METHODOLOGY This clinical audit aims to improve the quality of care of adult patients with T2DM in preventing ASCVD by utilizing the T2DM Clinical Practice Guidelines (CPG) 2020. A retrospective clinical audit was conducted using a convenient sampling method that involved 32 medical records from PPAT, Sungai Besi. Adults aged above 40 years with T2DM diagnosed for more than six months, and under active follow-up, were included. The criteria were based on the T2DM Clinical Practice Guidelines (CPG) 2020, with standards set at 90% and 50% based on literature reviews. RESULT A total of 32 medical records were audited. Most subjects were male (53%), with a median age of 54 years. 90.63% of T2DM adults were on statin therapy. The usage of statin therapy in T2DM patients above 40 years old is satisfactory and achieved the standard of 90%. However, only 20.69% were on high-intensity statin therapy and did not achieve the standard of 50%. CONCLUSION These issues need to be addressed by training healthcare providers. Enhancing clinic protocols to address relevant issues is imperative to enhance overall diabetes care, particularly ensuring appropriate utilization of statin therapy in T2DM patients who are either at high risk or very high risk of ASCVD.